Performance of Face to Face Absorption Signal on 2.4 GHz Low Profile Material Antenna - Irfan Mujahidin (Merdeka Malang University, 2020)
Based on sorts of conventional planar microstrip receiving wires, the adsorption exhibitions of comparing level confront to confront conformal microstrip radio wires are talked about and reenacted in this paper. In plan, each kind of microstrip 2.4 GHz square radio wire has three executives. For each kind of microstrip 2.4 GHz square radio wire, the measurement of the conductor square is 60mm x 60mm, and double equal accepting wires are identical taken on the superficies of the dielectric material, which is on the indicator transmit square radio wire. Concurring to the imitated comes almost, the working repeat of the essential kind of radio wire is around 2.4 GHz, the return loss wave extent are approximately 2.389 GHz-2.415 GHz and the directivity is about 0.6dBi and have vibration on radiation 3D pattern. Under face to face radiation two antenna conformal conditions, the microstrip .4 GHz square antennas keep the radiation performance microstrip antennas because its under or close 1 that necessary close with 100%.DOI : https://doi.org/10.26905/jeemecs.v3i2.4315